ROLE OF ANTIBIOTICS IN RAISED SERUM PROSTATE SPECIFIC ANTIGEN (PSA) (Journal of Medical & Health Sciences Review, 2025)
Background: The prostate-specific antigen (PSA) level is considered an essential diagnostic tool for detecting prostate cancer. The abnormal digital rectal examination (DRE) has been obviously reduced and biochemical result (elevated PSA) have augmented the indication of prostate biopsy over the past.Objective: The objective of this study is the comparison of PSA level in patients before and after four weeks antibiotics therapy.Material and Methods: Patients were evaluated with history, physical examination and urine C/S after prostatic massage and serum PSA through ELISA method. If PSA level was raised > 4ng/dl then antibiotic therapy was given on the basis of urine culture sensitivity. Patients with negative urine cuture tablet Ciprofloxacin 500mg BD was started for a period of four weeks. Serum PSA level repeated after completion of therapy, trans-rectal ultrasound (TRUS) guided biopsy was performed if serum PSA remained above 4ng/dl (ELISA method).Results: In present study, mean patient age was 64.0±10.1 year. (ranged, 45-85 year). Distribution of patients by urine C/S was as follows: No growth in 26 (65.0%) of patients, sensitivity to augmentin (Amoxicillin+Clavulinic acid) in 5 (12.5%), ciprofloxacin and levofloxacin 2 (5.0%) each, mixed growth 3 (7.5%), enoxabid and nitrofuratoin 1 (2.5%) respectively. Table-3 reveals the types of antibiotics given, majority of the patients i.e 31 (77.5%) received ciprofloxacin, followed by levofloxacin given in 2 patients (5.0%), augmentin (Amoxicillin+Clavulinic acid)  in 6 patients (15.0%) and nitrofuration in 1 patient (2.5%) (Table-3). Out of 40 patients, PSA level became normal in 21 patients (52.4%). Outcome of biopsy was as follows: focal chronic prostatitis 14 (70.0%), chronic prostatitis 4 (20.0%) and moderately differentiated adenocarcinoma 2 (10.0%). Before treatment mean serum PSA was 10.45±5.38 ng/ml and after treatment mean serum PSA decreased to 5.47±4.49 ng/ml.Conclusion: Antibiotics treatment for 4 weeks in patients with PSA level > 4 ng/dl, may decrease serum PSA significantly. This may help us in avoiding un-necessary prostatic biopsies and its complications.